A Study of Chinese Students’ Application to UK Universities in Uncertain Times: From the Perspective of Education Agents - Yang, Ying; Lomer, Sylvie; Lim, Miguel Antonio; Mittelmeier , Jenna (Journal of International Students, 2021)
This research investigates education agents’ practices with in-service Chinese applicants to UK universities in the context of information asymmetry. COVID-19 serves as a backdrop as an illustrative case of a period of high information uncertainty, which has generated severe challenges for the international higher education sector and on Chinese applicants’ plans to study overseas. This study reports on the findings from in-depth interviews with 16 Chinese agent consultants undertaken in nine cities across China in the immediate aftermath of the pandemic (May 2020). The findings indicate that education agents attempt to mitigate the information asymmetry and emotionally reassure applicants through a four-step information management process. Our contribution generates a new understanding of the role that education agents play in international students’ applications and mobility, voices that are often ignored but essential for international students’ decision-making processes and existing university recruitment services.